Perancangan Sistem Informasi Layanan Pembinaan Mualaf dengan Metode UTAUT - Erano, Bhirawa Atha Bassni; Putri, Raissa Amanda (Journal of Information System Research (JOSH), 2025)
In the context of the life of a convert, a person who has just embraced Islam or converted to Islam, must be given guidance and guidance to find out more about Islam. Providing convenience for converts to get complete information about the conversion coaching services provided by the Medan Tuntungan KUA, because the Medan Tuntungan Religious Affairs Office does not yet have a computerized system so that it makes time ineffective and inefficient in the process of converting to Islam and its coaching and therefore wants to create There are systems in the system that can simplify the process of converting to Islam, namely the registration process, activity schedule, coaching materials, and others. As well as facilitating the management of data on convert coaching participants, including personal information, attendance history and website-based coaching progress. It is important to have such data to reduce the possibility of data loss. This research uses qualitative methods by collecting data, namely observation, interviews, literature study and linked questionnaires. The system development method used is the waterfall method. And using the Unified Theory of Acceptance and User Technology (UTAUT) approach model is used to identify information system usage. The results of this research are a web-based information system for the Muslim Convert Development Service at KUA Medan Tuntungan using the Utaut mosque method which can help the management of the religious affairs office in managing information about converts and their guidance.